Pattern of antidepressant prescription at tertiary (mental hospital vs medical college) care centre of central India - Pal, V. S.; Kumar Mishra, Dheerendra; Rastogi, Pali (International Journal of Research in Medical Sciences, 2017)
Background: Western literature full of extensively study the antidepressant prescription pattern at different settings. Recently in Indian context multicentre study and individual centers reported pattern of antidepressant uses for management of depression. With the time newer antidepressant approved, with better understanding of evidence based pathogenesis of illness influence the treatment patterns. Mental hospital setting is different that medical college setting at least for stigma related issue. The aim of the research work was to study the pattern of antidepressant prescription at mental hospital and medical college settings. Methods: Cross-sectional assessments were done at mental hospital and medical college centers. Subjects diagnosed as depressive episode as per ICD 10, age >18 year included in study. Total 105 treatment seeking subject included in study from both centers Data was collected on socio-demographic characteristics, Clinical profile and prescribed medication. Results: 49 subjects from mental hospital, 56 subjects from medical college included in study. Mean age of study sample 39.27±12.96 vs 37.49±14.90 years respectively at mental hospital and medical college centers. Escitalopram prescribed 83.7% subjects, 53.3 % subjects receive monotherapy. L methyl folate and atypical antipsychotics was most commonly adjunctive medication with antidepressants. Conclusions: In sociodemographic differences subjects attending mental hospital belong to lower socioeconomic status compare to subject attending mental hospitals. There were no significant differences in prescription pattern of antidepressant medication for treatment of depressive episode. Escitalopram most commonly prescribed antidepressant and L methyl folate and atypical antipsychotics was most commonly used adjuvant with antidepressant medications.